The Collaborative Pedagogies of Solo Improvisation: Learning through Performance in Noise Music - Woods, Peter J. (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2022)
Although extant literature has argued for the pedagogical value of free improvisation within music education settings, these studies have largely overlooked how musicians develop their musical and sociocultural knowledges through this process of making music. In response, I use this paper to examine the mechanisms of learning within Thomson's notion of the performance as classroom. To do so, I situate this analysis within the noise music genre and analyze a video of American noise artists Crank Sturgeon to unveil how musical knowledges form within this performance. In doing so, I assert that the distributed and non-anthropocentric understanding of collaboration at the heart of noise music expands the borders of performance as classroom to engage not only the performer on stage but the audience and music making technologies in the process of developing a supposedly individual artistic practice.